Induction chemoradiotherapy achieves long-term recurrence-free survival in locally advanced pulmonary lymphoepithelioma-like carcinoma: a case report and literature review - Huang, Gengda; He, Hong; Fan, Yuting; Ren, Qinqin; Jiang, Huixin; Luo, Li; Guo, Li; Chen, Haiwen; Zhang, Jiexia (Frontiers in Immunology, 2025)
Pulmonary lymphoepithelioma-like carcinoma (pLELC) is a rare subtype of non-small cell lung cancer (NSCLC) that is closely associated with Epstein-Barr virus (EBV) infection. While radiotherapy after induction chemotherapy have shown marked efficacy in nasopharyngeal carcinoma (NPC), its effectiveness in pLELC remains uncertain. A female with stage IIIB pLELC was treated with 4 cycles of gemcitabine plus cisplatin, achieving partial response(PR), followed by radical radiotherapy. Patients achieved clinical complete response(CR) with recurrence-free for over five years. This case highlights the potential of induction chemotherapy as an effective treatment for locally advanced pLELC.